Re-defining Traditional Bazaar Areas and Shade Structures via Parametric Design Methods in the Memory of Urban Culture - Dinçer, Ahmet Emre; Bektaş, İbrahim; İyican, A. Bilgehan; Engin, Abdul Samet (ICONARCH International Congress of Architecture and Planning, 2017)
From past to present, by the beginning of shopping culture, people created common use areas to supply their needs or to sell products and goods. These spaces became socio-cultural areas which provided communication by getting together and answered various needs besides their economical purposes. By the advancement of societies in the meaning of creating civilization, shopping areas also went into a transition. This transition formed present shopping culture, reflected into space and building forms by naturally effecting matters of architecture and city planning. Thus, bazaar areas, which were open and portable in the past, have been transformed into stores, then organizing side by side they constituted markets and at the present time they created multistory shopping malls. Beside this, despite the change of shopping areas in our day, traditional open street alley bazaar culture continues under the name of “Neighborhood Bazaar” a little different from its first form. Nowadays, there is a need of providing some determined comfort conditions to the users for these street alley bazaars. Decreasing the effect of unfavorable weather conditions and providing supportive certain services and units (like WCs, security, cleanliness, etc.) are some of them. As a fundamental solution, without disengaging the user relations with the outside, shade structures are generally provided. Shade structures can support cleaning and similar jobs by gathering and using rainwater besides its purpose of protecting the user from bad weather conditions. Application examples of these systems are gradually increasing. However, it is necessary to develop new approaches, in order to stop these proposed shade structures, become prototypes, and to adapt the proposal to its environment and to increase diversity. In this study, a convenient shade structure and its alternatives, which are adapted to environmental conditions, were designed to create a sample model for other bazaar areas. In models, basically, folding design approaches were pursued. For production of these shade structure models, parametric modelling technics (Rhinoceros and Grasshoppers software) were used and different variations of model were generated. Chosen examples of models were evaluated in the aspect of feasibility. A comparison was made between the existing examples and our designed model. Ecological contributions of this model were also taken into consideration and harvestable rainwater amount by this system was calculated. Accordingly, advantages of the system to the bazaar area and to its environment were studied.